2010
DOI: 10.1093/nar/gkq588
|View full text |Cite
|
Sign up to set email alerts
|

Class-specific restrictions define primase interactions with DNA template and replicative helicase

Abstract: Bacterial primase is stimulated by replicative helicase to produce RNA primers that are essential for DNA replication. To identify mechanisms regulating primase activity, we characterized primase initiation specificity and interactions with the replicative helicase for gram-positive Firmicutes (Staphylococcus, Bacillus and Geobacillus) and gram-negative Proteobacteria (Escherichia, Yersinia and Pseudomonas). Contributions of the primase zinc-binding domain, RNA polymerase domain and helicase-binding domain on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 40 publications
1
17
0
2
Order By: Relevance
“…Bacillus subtilis DnaG initiation specificity was predicted to be similar to that of primases from other Firmicutes belonging to the Bacilli class (28). To test this hypothesis, two oligonucleotides that comprised all 64 possible trinucleotide sequences were initially used to assess template specificity, followed by trinucleotide-specific ssDNA oligonucleotides to verify template specificity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacillus subtilis DnaG initiation specificity was predicted to be similar to that of primases from other Firmicutes belonging to the Bacilli class (28). To test this hypothesis, two oligonucleotides that comprised all 64 possible trinucleotide sequences were initially used to assess template specificity, followed by trinucleotide-specific ssDNA oligonucleotides to verify template specificity.…”
Section: Resultsmentioning
confidence: 99%
“…RNA priming assays and denaturing high performance liquid chromatography (HPLC) analyses were conducted as previously determined for other mesophilic DnaG primases from Firmicutes that belong to the Bacilli class (28). Briefly, all RNA primer synthesis reactions were carried out in 100 µl of nuclease-free water containing 50 mM HEPES (pH 7.5), 100 mM potassium glutamate, 10 mM DTT, 2 µM ssDNA template, 40 mM magnesium acetate and 0.8 mM of each NTP and/or dNTP, unless otherwise specified.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the PDB template used by Phyre2 is 2AU3, the A. aeolicus primase [54]. The crystal structure of G. stearothermophilus DnaG primase contains a histidine at this position [50,80] and the multiple sequence alignment suggests that other Firmicutes also do. We hypothesized that the exposed lysine residue influences primase initiation specificity.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the primase of C. difficile has an unusual trinucleotide specificity, with a preference for 5′-d(CCC) (figure 5), which is similar to primase of A. aeolicus [74] but different from the specificity of primases from other Firmicutes or Gammaproteobacteria (5′-d(CTA), 5′-d(TTA), 5′-d(CTG)) [50]. The first two nucleotides in all of these trinucleotides are pyrimidines (C or T) and as a result the first two nucleotides in the RNA primer will be purines (G or A).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms, which are well known from the DNA duplication prior to prokaryotic cell division, are adapted to synthesize novel DNA molecules in vitro . While during replication of DNA in vivo , the DNA polymerase needs a short ribonucleic acid oligonucleotide to start with, provided by the enzyme primase (reviewed in [3]), during PCR in vitro these starter molecules are synthetic (the oligonucleotide primers). These primers define the starting points for DNA synthesis anywhere on the bacterial genome, regardless of an origin of replication.…”
Section: Polymerase Chain Reaction Some Basic Reflectionsmentioning
confidence: 99%